COMPARISON OF ACTIVE ISOLATED STRETCH AND POST ISOMETRIC RELAXATION FOR IMPROVING HAMSTRING FLEXIBILITY IN YOUNG HEALTHY ADULTS - Naweed, Jawad; Razzaq, Maria; Sheraz, Suman; Anwar, Nazish; Sadiq, Noman; Naweed, Saeeda (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the immediate, short term and long term effects of active isolated stretch versus post isometric relaxation on hamstring flexibility in young healthy adults. Study Design: Randomized controlled trial (trail number is NCT04024839). Place and Duration of Study: Islamabad Federal College, in the department of Doctor of Physical Therapy from Jan 2018 to Jul 2018. Methodology: Thirty five students were selected according to inclusion criteria and randomly assigned into two groups by lottery method 17 and 18 in each group respectively. Group A was given post isometric relaxation while group B was active isolated stretch. Age group between 18 to 25 year, male and female students with tight hamstring were included while neurological and orthopedic disorders were excluded. Active Isolated Stretch and Post Isometric Relaxation at baseline, after first and final exercise session were calculated immediately and short term effects while long term effects were calculated after two weeks of final session. Results: Active knee extension score for both hamstring muscles after 1st session showed statistical insignificant improvement for both legs (p=0.20 right and p=0.18 left). Active knee extension score after 2 weeks of exercises gave insignificant improvement in score for both legs (p=0.20 right and p=0.20 left). Similarly, Active Knee Extension score after all sessions showed insignificant improvement for both legs (p=0.49 right and p=0.88 left). There was no significant improvement for Active Knee Extension, lower extremity scale and sit and reach test with p=0.15. There were no differences between the effectiveness of both techniques i.e., Passive Isometric Relaxation and Active Isolated Stretch (p=0.58). Conclusion: Both techniques were equally effective in their immediate, short-term and long term effects on hamstrings flexibility.